JINOYATChILIKNI GEOGRAFIK JIHATLARINI TADQIQ ETIShDA GAT TEXNOLOGIYALARIDAN FOYDALANISh USULLARI (Fargʻona viloyati misolida) - Muxitdinov, I.I. (SCIENCE and SOCIETY, 2025)
This article examines the essence and significance of geographic information systems (GIS) technologies in crime analysis, methods of their analysis through mapping and "regionalization" of territories. The results showed the territorial distribution of crime and the identification of "hot spots," and practical recommendations were given for law enforcement agencies. The article, based on scientific sources, fully substantiates the role of GIS technologies in studying the geography of crime.